ANALISIS EFISIENSI INPUT USAHATANI PADI LADANG AKSESI UTAN ANTU DI DESA TUIK KECAMATAN KELAPA KABUPATEN BANGKA BARAT - Arifandi, Eni Karsiningsih, Rostiar Sitorus, dan (LPPM UBB, 2014)
ABSTRACTThe purpose of this research is to calculate the amount of income from upland rice farming of Utan Antu Accession in a single growing season in Tuik Village, to analyze what inputs have real effects on the production of the said upland rice farming, to analyze the level of price efficiency in the use of input in the said upland rice farming. This research was conducted in September 2013 in Tuik Village, Kelapa District, West Bangka Regency. The research method used was survey and sampling method used in thisstudy was simple random with a sample size of 39 sample farmers. The analysis method used was multiple linear regressions analysis using function production analysis by Cobb-Douglas. The research shows that a one year rice need of the farm families can be met with the farming product of Utan Antu Accession in Tuik Village, which is 417.15 kilograms with an actual income of minus Rp 2,150,570.73 per growing season. The inputs that have real impact on the production is fertilizer input at an error rate of 5 percent and workforce at an error rate of 1 percent. Pesticides input has nosignificant impact, the use of fertilizer and labor inputs was not efficient in terms of price efficiency analysis.Keywords: Efficiency, upland rice, Utan Antu Accession